Socio-science spirituality learning model for cultivating student spirituality and science process skills at Islamic schools - Rahmatika, Resty; Amin, Mohamad; Muhdhar, Mimien Henie Irawati Al; Suwono, Hadi (International Journal of Evaluation and Research in Education (IJERE), 2024)
Complementing science subjects with spirituality components is almost universal and is a significant requirement in religion-based schools. However, integrating spiritual components into science classes is challenging, particularly in inquiry-based problem-solving tasks. In this experiment, we modified inquiry learning and contextual teaching. We tested the efficacy of a combined model called the socio-science spirituality (3S) model on students’ spirituality and science process skills (SPS). Through a quasi-experiment, this learning model was applied in classes addressing the digestive system, additives and addictive chemicals, and the circulatory system. Following the 3S classroom implementation, we compared the mean pre- and post-test scores of the experimental and control groups using the analysis of covariance (ANCOVA) test and then assessed the relationship between spirituality and SPS in the classrooms using the Pearson-correlation test. The research found that spirituality and SPS were much higher and more prevalent in the experimental group compared to the control group. In the experimental class, there was also a link between spirituality and SPS. Theoretically, this research finding contributes to spiritual education and the development of SPS skills in science classes simultaneously. This research provides a unique way to prioritize the integration of spirituality in science learning. Practically, the research explain the details of the implementation of spirituality that can be applied to inquiry activities in science classes through the 3S model.